GAMBARAN POST-ACUTE COVID-19 SYNDROME PADA PASIEN PASCA TERINFEKSI CORONAVIRUS DISEASE 2019 - Arsita Devie, I Gusti Ayu Julia; Suarningsih, Ni Kadek Ayu; Rahajeng, Indah Mei; Widyanthari, Desak Made (Coping: Community of Publishing in Nursing, 2022)
Post-acute COVID-19 syndrome is a persistent symptom over a longer period among patients who have recovered from COVID-19. Prolonged COVID-19 symptoms have an impact on physical and psychological health. This study aims to determine the description of post-acute COVID-19 syndrome in patients post-infected with COVID-19. The research sample consisted of 30 post-treatment patients with COVID-19 who were selected using a non-probability sampling with quota sampling technique. The results showed that the average age of post-COVID-19 infected patients was 29 years and the majority were female. Most of them underwent treatment for COVID-19 through self-isolation (56,7%) with an average length of treatment of 12,8 days. The most commonly reported symptoms during or before being infected with COVID-19 were loss of taste and smell, cough, fever, fatigue, and sore throat. Meanwhile, symptoms that persist 1-2 weeks after being declared cured of COVID-19 infection which were commonly reported were fatigue, cough, loss of taste and smell, sore throat, and shortness of breath. Persistent cough symptoms with a characteristic cough with mucus or phlegm occurred in 26,7% of patients. Shortness of breath experienced 1-2 weeks after being infected with COVID-19, 83,3% of them experienced shortness of breath when doing activities in the mild category. In addition, the majority who experience symptoms of fatigue after 1-2 weeks after being infected with COVID-19 were in the severe category.